MEDIDAS DE DESPROPORCIONALIDADE NA DETEÇÃO DE SINAL EM FARMACOVIGILÂNCIA - Patrícia Dias; Carlos Fontes Ribeiro; Francisco Batel Marques (Revista Portuguesa de Farmacoterapia, 2014)
In pharmacovigilance, the detection of causal relationships between adverse events occurrence and drug exposure, besides safety signals generation, is mainly based upon spontaneous reporting systems which, in turn, generate large volumes of information. These systems allow the monitoring of all marketed drugs, in the “real world” conditions, over time periods, at relatively low costs. Traditional qualitative analysis of large databases can be extremely time and resource consuming, making quantitative analysis or data mining attractive. The techniques most often used to extract information are “disproportionality measures” which quantify the unexpected profile of the number of reports concerning a given pair adverse event-drug. These methods should be complementary and not substitutes of traditional strategies of signal detection. Potential identified signals, if relevant, should be evaluated complementarily with individual and clinical analysis and can lead to the generation of safety signals which may imply regulatory actions.